Dysregulation of Iron Homeostasis in the CNS Contributes to Disease Progression in a Mouse Model of Amyotrophic Lateral Sclerosis - Jeong, Suh Young (J Neurosci, 2009)
Amyotrophic lateral sclerosis (ALS), characterized by degeneration of spinal motor neurons, consists of sporadic and familial forms. One cause of familial ALS is missense mutations in the superoxide dismutase 1 (SOD1) gene. Iron accumulation occurs in the CNS of both forms of ALS; however, its contribution to the pathogenesis of ALS is not known. We examined the role of iron in a transgenic mouse line overexpressing the human SOD1(G37R) mutant. We show that multiple mechanisms may underlie the iron accumulation in neurons and glia in SOD1(G37R) transgenic mice. These include dysregulation of proteins involved in iron influx and sensing of intracellular iron; iron accumulation in ventral motor neurons secondary to blockage of anterograde axonal transport; and increased mitochondrial iron load in neurons and glia. We also show that treatment of SOD1(G37R) mice with an iron chelator extends life span by 5 weeks, accompanied by increased survival of spinal motor neurons and improved locomotor function. These data suggest that iron chelator therapy might be useful for the treatment of ALS.